Performance evaluation of multiple input-queued ATM switches with PIM scheduling under bursty traffic. - Ge Nong
In this letter, we analyze the performance of multiple input-queued asynchronous transfer mode (ATM) switches that use parallel iterative matching (PIM) for scheduling the transmission of head-of-line cells in the input queues. A queueing model of the switch is developed under independently, identically distributed, two-state Markov modulated Bernoulli processes bursty traffic. The underlying Markov chain of the queueing model is a quasi-birth-death (QBD) chain. The QBD chain is solved using an iterative computing method. Interesting performance metrics of the ATM switch such as the throughput, the mean cell delay, and the cell loss probability can be derived from the model. Numerical results from both the analytical model and simulation are presented, and the accuracy of the analysis is briefly discussed
Keywords: Markov chain; PIM scheduling; QBD chain; Asynchronous transfer mode; Bursty traffic; Cell loss probability; Head-of-line cells; Independently identically distributed system; Iterative computing method; Mean cell delay; Multiple input-queued ATM switches; Parallel iterative matching; Performance evaluation; Quasi-birth-death chain; Queueing model; Throughput; Two-state Markov modulated Bernoulli processes bursty traffic